The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12934-022-01748-x
|View full text |Cite
|
Sign up to set email alerts
|

Altering the fatty acid profile of Yarrowia lipolytica to mimic cocoa butter by genetic engineering of desaturases

Abstract: Background Demand for Cocoa butter is steadily increasing, but the supply of cocoa beans is naturally limited and under threat from global warming. One route to meeting the future demand for cocoa butter equivalent (CBE) could be to utilize microbial cell factories such as the oleaginous yeast Yarrowia lipolytica. Results The main goal was to achieve triacyl-glycerol (TAG) storage lipids in Y. lipolytica mimicking cocoa butter. This was accomplishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…of the desaturases can massively alter the fatty acid profile. 26 , 32 , 33 Our results show that urea can be used as a drop-in nitrogen source instead of ammonium sulfate without massively altering the storage lipid profile.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…of the desaturases can massively alter the fatty acid profile. 26 , 32 , 33 Our results show that urea can be used as a drop-in nitrogen source instead of ammonium sulfate without massively altering the storage lipid profile.…”
Section: Discussionmentioning
confidence: 72%
“…food oils. 26 In these cases, nitrogen starvation is used to trigger lipid production to achieve high lipid titers. Under nitrogen-limiting conditions, the obese strain (OKYL049) showed significant changes in C16:0 and C18:2 between the two nitrogen sources.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are still many barriers to settle for further improving the accumulation of nutritional fatty acids in Y. lipolytica , significant advances have been made. For example, many natural food substitutes, such as human milk fat substitutes and cocoa butter equivalents, have been produced by Y. lipolytica [ 96 , 97 ]. Nowadays, many emerging synthetic biology tools and gene editing technologies are on their way to become standard laboratory techniques for metabolic engineering of Y. lipolytica .…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…A part of the previous studies on Y. lipolytica enabled switching the fatty acid composition by metabolic engineering strategies. These approaches were mainly focused on the manipulation of the elongation and desaturation pathway [ 30 , 31 ]. Additionally, Ochsenreither et al [ 19 ] reported that temperature and the composition of the medium lead to variation in fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%